Business resilience in the Quindío agro-industrial cluster: a forward-looking approach based on business networks - Adriana María Flórez Laiseca; Elkin Argiro Muñoz Arroyave (Tendencias)
Introduction: This study examines the resilience of the Quindío agroindustrial cluster in the face of economic shocks, analyzing how integration and collaboration between firms, influence its adaptive capacity. Objective: To evaluate the impact of business networks on the resilience of the cluster, considering different levels of integration and their effect on the absorption of economic shocks and the diffusion of ideas. Methodology: A qualitative approach was used, complemented with business network simulations to model low and high integration scenarios. Results: Higher integration among cluster firms significantly strengthens their resilience to market shocks and facilitates access to knowledge and innovation. In addition, the importance of strengthening inter-firm linkages and R&D activities to enhance the competitiveness of the sector is highlighted.  Conclusions: It was found that, at different levels of integration, networks influence the cluster's capacity to absorb shocks and disseminate innovations, determining aspects to guarantee sustainability and competitiveness in the long term. This provides empirical evidence on clusters and highlights the need to strengthen business networks, in addition to offering guidelines for the design and formulation of territorial planning policies and instruments.